Postpartum depression and associated risk factors during the COVID-19 pandemic - Clayton J. Shuman; Alex F. Peahl; Neha Pareddy; Mikayla E. Morgan; Jolyna Chiangong; Philip T. Veliz; Vanessa K. Dalton (BMC Research Notes, 2022)
Abstract Objective To describe postpartum depression and associated risk factors among postpartum patients in the United States (US) between February and July 2020. This study used a cross-sectional descriptive design to collect survey data from a convenience sample of postpartum patients who lived in the US and delivered a live infant after the US declared COVID-19 a public health emergency. Results Our sample included 670 postpartum patients who completed an online survey inclusive of the Edinburgh Postnatal Depression Scale (EPDS) and selected demographic items (e.g. NICU admission status, infant gestational age, infant feeding method). In our sample, 1 in 3 participants screened positive for postpartum depression and 1 in 5 had major depressive symptoms. Participants who fed their infants formula had 92% greater odds of screening positive for postpartum depression and were 73% more likely to screen positive for major depressive symptoms compared to those who breastfed or bottle-fed with their own human milk. Participants with infants admitted to a NICU had 74% greater odds of screening positive. Each 1 week increase in weeks postpartum increased the odds of screening positive by 4%. Participants who worried about themselves and their infants contracting COVID-19 had 71% greater odds of screening positive.